ACTUAL APPROACHES TO THE ADAPTATION OF SEISMIC SENSORS FOR THE MAN-CAUSED TERRITORIES - S. Kravets, Nadiia; Malytskyy, D.; Astashkina, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the elucidation of experimentally tested methods for correcting the frequency range, amplitudes and noise levels for seismic sensors. Increasing the level of sensitivity of the registration system in a certain frequency range allows flexibly and in a short time to study the timing of microearthquakes in different geological structures and assess seismic parameters, control the development of natural karst phenomena and man-made cracks and deformations. The method of expanding the limits of application of common seismic transmitters type SM-3 and (SM-3 KV) in the seismic channels of portable seismic stations used in Ukraine is presented to solve a number of problems of seismology in technogenic-loaded regions with a high level of industrial average daily noise components. The article presents some results of registration of seismic signals performed by the information collection system using additional corrected seismic sensors SM-3 with extended frequency range in the low frequency range of the spectrum 0.1–3 Hz, installed at Carp-Lviv-2.